Identification and Stylistic Analysis of the Artistic Expression on Opa, Yoruba Sculptural Verges - Michael Olaniyi Ajadi (Yoruba Studies Review)
Opa is an emblematic Yoruba sculptural verge and preserved transcendence expressional art amongst the social group in order to describe hierarchical structure in ranking chiefs, religious cults’ priests/priestesses and aged right. Significantly, time-scale conscious and in-depth exploration of the hierarchical motifs on diverse verges and artistic formats of integrated motifs have not been considered using deco-hierarchical structures analysis. The visual artistic expression of verges sculptural forms demands contextual exploration to give meaningful time-scale oriented written reports that could clear up vague impressions towards different structures. For this conspicuous fact, a study of Yoruba sculpturesque verges will crystallize metonymical written explanations of motifs that suggest the power structure of the life of the Yoruba. The paper, therefore, examines the class-conscious format of images, motifs, and symbols unified on diverse emblematic verges for exploration of distinctive features of chieftains’ status, stylistic expression and interpretation of cults’ art in the Yoruba culture. Analytical review and critical appraisal methodologies were utilized for diverse verges; pictures were collated for critical examination of stratified motifs and symbols with the objectives of contextual and conceptual analyses. Findings unveiled artists’ expression towards this symbol of superiority which exists within the hierarchical structure of chieftaincy and religious cults’ orientations of Yoruba gods. However, it is apparent from studied verges that fastidiously effort given to the balance of patterns, motifs, and forms through professionalism and prowess suggest Yoruba ways of life.